2021
DOI: 10.1063/5.0062408
|View full text |Cite
|
Sign up to set email alerts
|

Vapor pressures and vapor phase compositions of choline chloride urea and choline chloride ethylene glycol deep eutectic solvents from molecular simulation

Abstract: Despite the widespread acknowledgment that deep eutectic solvents (DESs) have negligible vapor pressures, very few studies in which the vapor pressures of these solvents are measured or computed are available. Similarly, the vapor phase composition is known for only a few DESs. In this study, for the first time, the vapor pressures and vapor phase compositions of choline chloride urea (ChClU) and choline chloride ethylene glycol (ChClEg) DESs are computed using Monte Carlo simulations. The partial pressures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…The charges of choline chloride were scaled by a factor of 0.8 and 0.9 in reline and ethaline, respectively. 55 , 56 This implementation yields accurate predictions for various thermophysical properties of DES as shown by Perkins et al, 55 , 56 Salehi et al, 24 and Celebi et al 26 , 27 , 57 The Lennard-Jones interaction parameters between unlike species were computed using the Lorentz–Berthelot combining rules. 58 All force field parameters and the functional forms of the bonded and nonbonded terms used in this study are available in the Supporting Information .…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The charges of choline chloride were scaled by a factor of 0.8 and 0.9 in reline and ethaline, respectively. 55 , 56 This implementation yields accurate predictions for various thermophysical properties of DES as shown by Perkins et al, 55 , 56 Salehi et al, 24 and Celebi et al 26 , 27 , 57 The Lennard-Jones interaction parameters between unlike species were computed using the Lorentz–Berthelot combining rules. 58 All force field parameters and the functional forms of the bonded and nonbonded terms used in this study are available in the Supporting Information .…”
Section: Methodsmentioning
confidence: 92%
“…The DES were modeled using the GAFF 53 force field consistently with our previous studies. 21 , 24 , 26 , 27 , 54 For choline, urea, and ethylene glycol, 1–4 interactions were scaled by a factor of 0.5 for both Lennard-Jones and Coulombic interactions. The charges of choline chloride were scaled by a factor of 0.8 and 0.9 in reline and ethaline, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Ferreira et al followed a similar procedure to calculate Δ H vap values for CCPro in separate work 143 . In general, while experimentally measured vapor pressures of DESs are quite close to the vapor pressures of their respective pure HBDs, 140 MD simulations have provided evidence that some proportion of the HBA components should be present in the gas phase of DESs 144 …”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Both reline and ethaline DESs exhibit good methane capturing ability . Another study performed by the same group employed MC simulations to compute the vapor phase compositions and vapor pressures of reline and ethaline . This study showed that HBD in both the DESs dominates the vapor phase, suggesting the volatile nature of HBD .…”
Section: Introductionmentioning
confidence: 95%
“…Another study performed by the same group employed MC simulations to compute the vapor phase compositions and vapor pressures of reline and ethaline . This study showed that HBD in both the DESs dominates the vapor phase, suggesting the volatile nature of HBD . Vlugt and co-workers performed molecular dynamics (MD) simulations to predict solubility parameters, enthalpy of vaporization, and vapor phase composition for various [Ch]­[Cl]-based DESs .…”
Section: Introductionmentioning
confidence: 99%